Bioactive compounds produced by gut microbial tannase: implications for colorectal cancer development - López de Felipe, Félix; de las Rivas, Blanca; Muñoz, Rosario (Frontiers in Microbiology, 2014)
The microorganisms in the human gastrointestinal tract have a profound influence on the transformation of food into metabolites which can impact human health. Gallic acid and pyrogallol are bioactive compounds displaying diverse biological properties, including carcinogenic inhibiting activities. However its concentration in fruits and vegetables is generally low. These metabolites can be also generated as final products of tannin metabolism by microbes endowed with tannase, which opens up the possibility of their anti-cancer potential being increased. Patients with colorectal cancer display an imbalanced gut microbiota respect to healthy population. The recent use of next generation sequencing technologies has greatly improved knowledge of the identity of bacterial species that colonize non-tumorous and tumorous tissues of colorectal cancer patients. This information provides a unique opportunity to shed light on the role played by gut microorganisms in the different stages of this disease. We here review the recently published gut microbiome associated to colorectal cancer patients and highlight tannase as an underlying gene function of bacterial species that selectively colonize tumorous tissues, but not adjacent non-malignant